EVALUATION OF MAIZE ACCESSIONS UNDER LOW TEMPERATURE STRESS AT EARLY GROWTH STAGES - S. Bano; M. Aslam; M. Saleem; S. M. A. Basra; K. Aziz (Journal of Animal and Plant Sciences, 2015)
Maize is a very important cereal and grown globally across wide range of altitude and latitude. Among abiotic stresses, low temperature is a sever threat for spring maize in Pakistan during early growth stages. This study was planned to sort out tolerant and susceptible maize accessions by evaluation of available maize germplasm against low temperature stress and assessment of genetic diversity among them. At low temperature stress, early emergence of maize and improved photosynthetic performance are the good indicators of early seedling stand. The objectives of this study were (i) to characterize maize accessions for early emergence and photosynthesis related traits at 10/08˚C (day/night), (ii) to explain relationship between different low temperature related traits and (iii) to identify best performing accessions under low temperature to be used in hybridization to evolve chilling tolerant hybrids. The effect of low temperature stress was studied on emergence potential, root/shoot ratio, chlorophyll a, chlorophyll b, β-carotenoids and ascorbic acid contents. Significant differences were observed among maize accessions for studied traits under low temperature stress. Using biplot analysis, genetically distant accessions showed variable responses to low temperature stress. Maize accessions; 2(EV-7004Q), 5(F-150), 23(F-118), 26(B-308), 46(EV-338), 34(POP-2007), and 18(EV-329) showed superior performance for emergence whereas, 69(EV-134), 59(B-304), 56(F-151), 58(B-313), 73(F-143) and 63(F122) performed well regarding post emergence parameters by maintaining higher values for subjected traits. Chlorophyll contents reflected photosynthesis efficiency of any plant and showed significant positive association with emergence of plants therefore proved a good indicator against low temperature stress. Selection on the basis of combination of emergence related traits and chlorophyll contents provided a sound base to identify early emergence and healthy seedling development.
Keywords: Maize; Low temperature stress; Physiological evaluation; Correlation analysis; Biplot analysis